Rola uczelni wyższych w przygotowaniu przyszłych nauczycieli do współpracy z rodzicami = The role of higher education institutions in the preparation process of the future teachers to cooperate with parents - Nowosad, Inetta; Pietrań, Klaudia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article undertakes the issue of teachers preparation to cooperate with parents. It mostly concentrates on the role played by higher education institutions in this important area of functioning of the future tutors. The issue referred to, although it has occupied an important place in Polish pedagogy, still remains undervalued in the process of future teachers education. The analysis of education programmes and the programmes of trainings in state, higher education schools clearly points to the insufficiency of both theory and practice concerning the cooperation between the teachers and the parents, and it further stresses further necessity to improve this important area.
Keywords: szkolnictwo wyższe; uczelnia wyższa; współpraca z rodzicami; kształcenie nauczycieli